2008
DOI: 10.2131/jts.33.447
|View full text |Cite
|
Sign up to set email alerts
|

Strain differences in hepatic cytochrome P450 1A and 3A expression between Sprague-Dawley and Wistar rats

Abstract: -Expression of hepatic cytochrome P450 (CYP) isoforms was compared in Sprague-Dawley (SD) and Wistar (WI) rats, which are commonly used strains in preclinical studies. Basal CYP1A1, -tively). Treatment with phenobarbital, a potent CYP inducer, increased the predominance of expression increased microsomal total P450 contents and smooth-surface endoplasmic reticulum in the centrilobular -rats exhibited predominantly arylhydrocarbon receptor, pregnane X receptor, and constitutive androstane WI rats was observed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 31 publications
0
25
0
1
Order By: Relevance
“…Testosterone hydroxylation activity in hepatic microsomes was determined by measuring 6β-, 16α-and 16β-hydroxytestosterone resulting from hydroxylation of testosterone according to a published high-performance liquid chromatography (HPLC) method (Imaoka et al, 1989;Kishida et al, 2008) at 1 mM testosterone (testosterone, hydroxytestosterone; Sigma Chemical Co., St. Louis, MO, USA). The 6β-, 16α-and 16β-testosterone hydroxylation activities are known as indicators of the enzyme activity of CYP3A, CYP2C and CYP2B, respectively, which are major CYP subfamilies.…”
Section: In Vitro Assay Using Hepatic Microsomes Prepared From Rats Tmentioning
confidence: 99%
“…Testosterone hydroxylation activity in hepatic microsomes was determined by measuring 6β-, 16α-and 16β-hydroxytestosterone resulting from hydroxylation of testosterone according to a published high-performance liquid chromatography (HPLC) method (Imaoka et al, 1989;Kishida et al, 2008) at 1 mM testosterone (testosterone, hydroxytestosterone; Sigma Chemical Co., St. Louis, MO, USA). The 6β-, 16α-and 16β-testosterone hydroxylation activities are known as indicators of the enzyme activity of CYP3A, CYP2C and CYP2B, respectively, which are major CYP subfamilies.…”
Section: In Vitro Assay Using Hepatic Microsomes Prepared From Rats Tmentioning
confidence: 99%
“…Subsequently, Wen et al (2009) showed that NVP is metabolized to a GSH adduct by CYP3A4. Dexamethasone is a highly effective inducer of hepatic CYP3A1 in male Wistar rats and also induces CYP3A2 (Kishida et al, 2008). In addition, 2-and 12-hydroxylations of NVP catalyzed by CYP3A isoforms, as represented by human CYP3A4 and CYP3A5 (Erickson et al, 1999), are potentially bioactivation pathways through the generation of reactive epoxide and quinone methide intermediates (Chen et al, 2008), respectively.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The LD50 was determined by linear regression analysis using the SPSS Science statistical software (v. 15 …”
Section: Discussionmentioning
confidence: 99%
“…the authors administered the extract orally for 90 days at doses of 1,000, 100, and 10 mg/kg/day; however, their study did not report that the extract produces a modulator effect. Some of the cytochromes studied so far include the following: 1A1 Kishida et al (2008) demonstrated that DEX is a selective inducer of CYP3a1, and that this induction is favored in Wistar rats. One of the strengths of the present study is that all of the groups were maintained, and that the same administration route was employed (Badal et al, 2011;Kondo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%